1997
DOI: 10.1093/brain/120.7.1105
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomigraine with temporary neurological symptoms and lymphocytic pleocytosis. A report of 50 cases

Abstract: This is the first large series, comprising 50 patients who suffered a total of 164 episodes, of pseudomigraine with temporary neurological symptoms and lymphocytic pleocytosis (PMP syndrome). Onset of PMP was between the ages of 14 and 39 years and was most frequent in males (68%). Eight males (24%) and five females (31%) had a personal history of migraine. One-quarter had had a viral-like illness up to 3 weeks prior to the onset of the syndrome. The clinical picture consisted of one to 12 episodes of changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
243
4
30

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(291 citation statements)
references
References 21 publications
14
243
4
30
Order By: Relevance
“…This was supported by investigations including imaging studies and normal CSF-PCR. The patient's EEG also did not reveal any focal slowing, a finding contrary to other studies, 6 although theta range waves were seen. Generalized slowing on the EEG during acute stage has been reported.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was supported by investigations including imaging studies and normal CSF-PCR. The patient's EEG also did not reveal any focal slowing, a finding contrary to other studies, 6 although theta range waves were seen. Generalized slowing on the EEG during acute stage has been reported.…”
Section: Discussioncontrasting
confidence: 99%
“…[2][3][4] Its aetiology still remains obscure, with researchers implicating immunogenic responses 5,6 and viral infections 7 as probable causations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study performed gene investigation in 8 patients in whom clinical findings suggested PMP, and reported that there were no abnormalities in the CACNAIA gene as observed in patients with FHM (11). In addition, diseases such as viral meningoencephalitis, granulomatous meningitis, neural syphilis, central infection with Borrelia or Mycoplasma, collagen disease-related angitis, cancerous meningitis, and Mollaret meningitis should be differentiated from PMP (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Memory disturbance in this patient continued for more than three weeks, although the duration of neurological deficits in HaNDL usually lasts less than three days (3). This syndrome was first described by Bartleson et al in 1981 (1).…”
mentioning
confidence: 55%
“…Recently, reports of patients with syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL), previously termed pseudomigraine with lymphocytic pleocytosis (PMP), have been increasing in number (1)(2)(3)(4)(5). However, due to the clinical similarities, other diagnoses such as familial hemiplegic migraine (FHM), neuroborreliosis, neurosyphilis, neurobrucellosis, mycoplasma, meningitis, granulomatous and neoplastic arachnoiditis, encephalitis, and CNS vasculitis should be considered (6).…”
mentioning
confidence: 99%